Analyzing Precipitation Changes in the Northern Tip of the Antarctic Peninsula during the 1970-2019 Period - Carrasco Cerda, Jorge Fernando; Cordero, Raul R. (My University, 2020)
Five decades of precipitation data are available from the Chilean Antarctic weather stations located in the northern tip of the Antarctic Peninsula. Data include daily accumulation and type of precipitation registered at the time of the observation at the Meteorological Antarctic Center located at Base Eduardo Frei Montalva, King George Island. This information allowed us to analyze not only the precipitation accumulation changes (always questionable in cold and windy regions) but also changes in precipitation days and precipitation phases (rain versus snow). The expo nential filter was applied to the monthly data to obtain decadal-like changes. The analysis revealed an overall increase in precipitation from 1970 to the early-1990s 60 +/- 7 mm (10 year)(-1) (p < 0.05) and 31 +/- 4 mm (10 year)(-1) (p < 0.05) and a negative trend between 1991 and 1999 with decreasing precipitation of -95 +/- 9 mm (10 year)(-1) (p < 0.05). On the other hand, while an increase in precipitation events also took place from 1970 to the early-1990s, there was a decreasing trend in precipitation events during the 2010s. This implies that the positive trend in precipitation accumulation registered during this period is due to the increasing extreme precipitation events. The precipitation type analysis shows an increase (decrease) in snow (rain) events from around the mid-1990s to mid-2010s during the summer season. These opposite trends were related to the summer cooling affecting the AP region.
Keywords: antarctic peninsula; precipitation; snow event; rain event; exponential filter